"I Have Been Bullied at Workplace!": A Qualitative Study on Italian Employees' Stories. (30th July 2018) - Caputo, Andrea
Abstract: The present study explored some common thematic domains which characterized workplace bullying stories of adult Italian participants. Emotional Text Analysis was performed on 28 workplace bullying stories in order to detect the main themes (cluster analysis) and latent factors (correspondence analysis) emerging in bullied workers' narratives. Five thematic domains were detected in the textual corpus ( p < .05, at 95% confidence level), which are respectively referred to as: organizational constraints (14.10%), treatment discrimination (10.04%), unjust accusations (30.77%), emotional abuse (14.53%), and job duty changes (30.56%). Four latent factors explained the overall data variance: Sense of precariousness (F1, 34.38% of variance), lack of recognition (F2, 26.35%), feeling of exclusion (F3, 23.01%) and job disengagement (F4, 16.27%). From the emotional experience shaping the relationship between bullied workers and their work environments, this research study allows the identification of some organizational situations that are "at risk" for workplace bullying in order to promote better organizational health.